Psychological Symptoms and Quality of Life After Simultaneous Kidney and Pancreas Transplantation. Issue 5 (May 2020) - Nijhoff, Michiel F.; Hovens, Jacqueline G.F.M.; Huisman, Sasja D.; Ringers, Jan; Rabelink, Ton A.J.; de Fijter, Hans J.W.; van der Boog, Paul J.M.; de Koning, Eelco J.P.
Abstract : Background: Patients that have undergone successful simultaneous pancreas/kidney (SPK) transplantation attain normoglycemia and are free from dialysis. However, only a minor improvement in quality of life (QOL) has been demonstrated. Here, we evaluated the role of psychological symptoms in QOL after SPK transplantation. Methods: We assessed patients with type 1 diabetes and end-stage renal disease waitlisted for SPK transplantation (pre-SPK, n = 47), and recipients of an SPK transplant (post-SPK, n = 72). Matched patients with type 1 diabetes without end-stage renal disease were included as reference group (type 1 diabetes [T1D] reference group, n = 42). The brief symptom inventory (BSI) was used to measure psychological symptoms. The Short Form-36 (SF-36) was used to determine QOL. Results: Post-SPK patients scored slightly better on the SF-36 than pre-SPK patients ("General health" 47.2 ± 23.1 versus 37.5 ± 18.1 [ P = 0.017]). In the T1D reference group, this score was 60.6 ± 22.3. Post- and pre-SPK patients had similar BSI scores (0.54 ± 0.55 and 0.45 ± 0.42, respectively [ P = 0.34]). This score was better in the T1D reference group (BSI score 0.32 ± 0.33). The BSI score inversely correlated with the SF-36 (r = −0.61, P < 0.001). Conclusions: Psychological symptoms are prevalent in both pre-SPK and post-SPK patients and could play an important role in the reduced QOL observed in these groups. Abstract : Supplemental Digital Content is available in the text.